PWM Inverter for Electric Drive Train Application - Abas, Mohd Amir (1999)
Controlling AC power load using DC supply requires complex design and circuit. Basically the controlling system comprises of low power control unit, inverter and the load. Multiple Pulse Width Modulation (MPWM) technique was used for controlling the control unit design as it gives low harmonic distortion compared with other types. Six MPWM signals were used to trigger the six channels in inverter circuit and all the signals were synchronous to avoid short circuit in inverter circuit. The design of the MPWM was simplified with an IC IR2130, which provided matched voltage trigger, adequate dead time for low and high channels and over current shut down. In inverter circuit design the main component in controlling the high current flow from DC supply to load is power device. There are various power devices available in the market but IGBT was chosen due to its high current rating and simple triggering process. Apart from single IGBT with high current rating being used in each channel; paralleling several IGBTs is also the technique that can be used to increase the power conversion in inverter circuits and to reduce the cost of design. It is evident that by paralleling several low current power devices, the amount of current produced equates the single high current power device. For the AC load, three-phase squirrel cage AC motor was chosen after comparing with other types of motors as it provides several advantages in terms of being robust, cheap and maintenance free. Overall result showed there was smooth control of AC motor using single configuration technique compared to using parallel configuration technique. Further investigations are required especially on the use of parallel configuration technique with IGBT as power device and also in simplifying the complex snubber circuit, needed for protecting power devices in inverter circuit from high current and voltage transients.